APPLICATION OF AUTOMATION PLANTING SYSTEM AT GREEN HOUSE IN IMPROVING PLANT QUALITY - Rahmi Balqis; Abdullah Abdullah (Universitas Islam Negeri Sumatera Utara Medan, 2020)
Research has been done to application of automation planting system at green house in improving plant quality which aims to help facilitate the work of farmers and get maximum crop yields. In this case Green House is simulated using acrylic boards with an area of 80 cm × 50 cm × 50 cm. The component used to detect temperature and humidity is the DHT 11 sensor. The air temperature and humidity control system is carried out by fans and incandescent lamps. Then for watering plants based on the time read in real time used Real Time Clock DS1307, and for soil moisture sensor used sensor YL-69 where soil moisture on the sensor is 0-100%. All data will be displayed on the LCD display 2 × 16. System testing is conducted by observing the system function in some time conducted from 05.00 am to end at 17.30 pm. At 07.05 and at 17.02, the watering of plants will be done in all directions. If the DHT 11 sensor detect a temperature above 32°C, the microcontroller activates the ventilation and peltier fans to neutralize the temperature inside the green house. Whereas if the temperature is detected below 27°C and above 26°C then lamp 1 will turn on and if the temperature is below or equal to 26°C then lights 1 and 2 will be activated until the temperature returns to normal which is between 27°C - 32°C. Last testing, if the sensor reads soil moisture below 60% then watering of plants will be done to the detected dry soil.